Apropriação de áreas públicas em Aparecida de Goiânia - Uso, abandono e gestão na cidade atual - Souza, Maria Ester de (2014)
Understanding the city, is not only challenging, but also necessary for both the maintenance of positive points and the modification of what may seem to be out of the city managers and inhabitants control. Qualifying the urban landscape is the desire of every one. However, watching legal and administrative disputes related to occupation or preservation of areas considered public has become a commonplace. This research analyzed the process of occupation of public areas located in two boroughs in the city of Aparecida de Goiânia, called Setor Mansões Paraíso and Colina Azul as a case study. Identify what the current role of the city public area is; identify the kinds of usage practiced in the Municipal Public Areas – APMs existing in these two districts; evaluate the production process of the intra-urban space from their occupation date to the present day and understand how the appropiation of these areas occurred were the objectives of this research. In order to have a complete view of the structuring process of these two areas, data were collected from the public, federal and municipal agencies, as well as visits, photographic records, elaboration of maps, drawings, interviews, news clippings made in printed newspaper, queries to specific laws, participation in events of the studied communities. The idea that a relevant analysis is inseperable from the observation of the political-economic and socio-cultural relations of a particular group of people at a certain time, guided the reading and understanding of t he collected data of this research. It was possible to conclude that public policies, forms of management and appropriation are defining elements to the urban landscape.